POLA KEMITRAAN MANGGIS BERBASIS EKSPOR DI DESA PADANGAN KABUPATEN TABANAN - Merlin Mei; Nyoman Yudiarini; Luh Putu Kirana Pratiwi (AGRIFARM (Jurnal Agribisnis dan Sosial Ekonomi Pertanian), 2022)
The mangosteen commodity is one of Bali's leading local products which is quite popular in the export market in China. The high market demand for mangosteen has led to a partnership between a group of mangosteen farmers and a mangosteen export company to meet market demand. This research aims to find out the following: (1) The pattern of partnership that occurs between PT Radja Manggis Sejati and a group of mangosteen farmers; (2) Rights and obligations of both parties; (3) The efficiency of the partnership between the two; (4) Obstacles faced by the partnership. The results show that; (1) The partnership is a partnership subcontract pattern; (2) The rights and obligations of both parties must be obeyed in accordance with the agreement that has been agreed upon; (3) The partnership between PT Radja Manggis Sejati and the mangosteen farmer group has been efficient; (4) The obstacles faced by PT Radja Manggis Sejati in this partnership were the poor quality of the mangosteen produced by the farmer group and fraud committed by the farmer group, while the obstacles faced by the farmer group were delays in payment by PT Radja Manggis Sejati and delays in the price of raw materials .